Craniofacial and extracraniofacial anomalies in craniofacial macrosomia: A multicenter study of 755 patients. Issue 8 (August 2017) - Caron, Cornelia J.J.M.; Pluijmers, Britt I.; Wolvius, Eppo B.; Looman, Caspar .W.N.; Bulstrode, Neil; Evans, Robert D.; Ayliffe, Peter; Mulliken, John B.; Dunaway, David; Padwa, Bonnie; Koudstaal, Maarten J.
Abstract: Purpose: Craniofacial microsomia (CFM) is a congenital malformation of structures derived from the first and second pharyngeal arches leading to underdevelopment of the face. However, besides the craniofacial underdevelopment, extracraniofacial anomalies including cardiac, renal and skeletal malformation have been described. The aim of this study is to analyse a large population of patients with regard to demographics, typical phenotypes including craniofacial and extracraniofacial anomalies, and the correlations between the different variables of this condition. Material and methods: A retrospective study was conducted in patients diagnosed with CFM with available clinical and/or radiographic images. All charts were reviewed for information on demographic, radiographic and diagnostic criteria. The presence of cleft lip/palate and extracraniofacial anomalies were noted. Pearson correlation tests and principal component analysis was performed on the phenotypic variables. Results: A total of 755 patients were included. The male-to-female ratio and right-to-left ratio were both 1.2:1. A correlation was found among Pruzansky–Kaban, orbit and soft tissue. Similar correlations were found between ear and nerve. There was no strong correlation between phenotype and extracraniofacial anomalies. Nevertheless, extracraniofacial anomalies were more frequently seen than in the 'normal' population. Patients with bilateral involvement had a more severe phenotype and a higher incidence of extracraniofacial and cleft lip/palate. Conclusion: Outcomes were similar to those of other smaller cohorts. Structures derived from the first pharyngeal arch and the second pharyngeal arch were correlated with degree of severity. Extracraniofacial anomalies were positively correlated with CFM. The findings show that bilaterally affected patients are more severely affected and should be approached more comprehensively.